Simulasi Model Sambungan Mekanis dengan Menggunakan Coupler Untuk Beton Pracetak - Rosyidah, Anis; Edistria, Ega; Wijaya, Bunga Shafira (Department of Civil Engineering, Diponegoro University, 2023)
The use of mechanical joints can improve the performance of the connection and make the time more efficient. The purpose of this study was to determine the maximum tensile force, failure pattern and effect of epoxy thickness on the maximum tensile force, epoxy-bar bonding stress, and epoxy-coupler bonding stress of each splice type Grouted Coupler Connector. The research specimens were 6 pieces with varying thicknesses of epoxy and diameter of reinforcing steel. Software that supports the pullout test simulation is ANSYS and the research data processing method uses Simple Linear Regression Analysis. The output from the pullout test simulation is the maximum tensile force with a thickness of 25mm epoxy on the reinforcing steel D16, D22, and D25 of 91.156 kN; 148,090 kN, and 203,295 kN. All the test specimens have an epoxy coupler slip failure pattern. And the concluded from the simple linear regression analysis is a significant effect between the thickness of the epoxy on the maximum tensile force and bond stress, with a negative regression coefficient value. The optimum value of using thick epoxy with a varying diameter of reinforcing bars is 25mm.